A FORMAÇÃO CONTINUADA E A DISCALCULIA DO DESENVOLVIMENTO: REFLEXÕES SOBRE UMA PERSPECTIVA COLABORATIVA - CORDEIRO, CINTIA APARECIDA BODNAR (2023)
Continuous training is essential for teachers to complement their studies and delve into certain topics that are present in the classroom, especially those related to the teaching and learning of Mathematics. Therefore, the general objective of this research is to analyze how Continuing Collaborative Training in Developmental Dyscalculia can contribute to teaching practices. This study is justified given the difficulties encountered by teachers who work with students who have learning disorders in mathematics. To this end, the research has a qualitative approach, since within the scope of data collection and results there is no concern for quantitative values. The collaborative continuing education had the participation of two Mathematics teachers and interventions were carried out at school during after-school hours with a student who showed signs of Dyscalculia through games and manipulative objects. Considering the results of the research, collaborative training is ideal, since it is a training process between peers and, therefore, much more productive, since the training is consolidated through dialogues, discussions and reflections in and on the practice. It is important to highlight that, although the student investigated in this research does not yet have all the criteria for a definitive report, showing only signs of Developmental Dyscalculia, it is essential that the teacher has solid training that equips him for an inclusive future practice. Furthermore, this research resulted in an educational product entitled (Collaborative Continuing Training Guide on Developmental Dyscalculia).